QUALITY CONTROL AND IN-VITRO STUDY RELEASE BEHAVIOUR OF EURYCOMANONE IN HERBAL PRODUCTS SUPPLEMENT IN CAPSULE FORM - Zainol, Noorazwani (International Journal of Psychosocial Rehabilitation, 2020)
Controlled releasedelivery system of active ingredients has a significant effect on their pharmacological activity. In fact, it is considered as one of the most important quality control test to predict their bioavailability. In this study the in-vitro study release behaviour was carried out using dissolution testing apparatus USP type-11 and submit to an independent model methods using time point approach whereby the percentage drug releases at a given time were determined. Three brands (TA, TB, TC) of herbal product supplements from different manufacturers which consist of Eurycomanone as active ingredients were compared. Brand TS is a pure extract of Eurycomanone used as a benchmark. The parameters employed to compare in-vitro study release behaviour are different dissolution media namely 0.1 N HCl, 30% EtOH, acetate buffer (pH 4.8) and phosphate buffer pH 6.8 for each brands for 105 minutes. Samples were withdrawn at 15 minutes time interval and analysed for the Eurycomanone release by using HPLC technique. Content of the Eurycomanone for brand TA and brand TS analysed via HPLC were the highest.When submitted to in-vitro release study, the release rate of Eurycomanonein brands TA was the highest in both acidic and alkaline medium (0.1 M HCl and 0.1 M PBS medium)while the release rate of Eurycomanonein brands TB was the highest in the alkaline medium compared to acidic medium. Amongst the three sample, brand TC showed the lowest released rate of Eurycomanone in all medium.The highest percent of drug release at a given time (Y30) for brand TA, brand TB and brand TC were 39.7% (0.1 M HCl), 33.5% (0.1 M PBS) and3.2% (0.1 % PBS), respectively. In this study, both results from in-vitro released study and HPLC testwere compliment and Eurycomanone used as chemical marker could be applied for quality control for the development of herbal products supplements in markets.